THE ROLES OF TEACHERS AND STUDENTS IN THE ESTABLISHMENT OF CLASSROOM RULES - Recep ATICI (Fırat University, 2019)
Rules are necessary to maintain the social order. Rules are also required to carry out efficient training and education within schools and classrooms. Classroom rules have to be adopted and followed. Thus, an increase in the quality of the education will also be ensured. At the same time, rules bring along objectivity. Teachers interact with each student in an objective manner within the class, in accordance with these rules. Awards granted and penalties imposed on the students, allow them to extricate themselves from in